2015
DOI: 10.5812/ircmj.17(4)2015.28091
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Grade of Acute Cholecystitis by Plasma Level of C-Reactive Protein

Abstract: Background:Acute cholecystitis is the most common complication of gallbladder stones. Today, Tokyo guidelines criteria are recommended for diagnosis, grading, and management of acute cholecystitis.Objectives:We aimed to evaluate the levels of C-reactive protein (CRP) at different cut-off values to predict the severity of the disease and its possible role in grading the disease with regard to the guideline.Patients and Methods:This is a retrospective study, analyzing 682 cases out of consecutive 892 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
2
18
0
2
Order By: Relevance
“…These findings confirmed the observation that AAC was concomitant with acute hepatitis rather than being induced by intrahepatic cholestasis . The correlation between the C‐reactive protein concentration in the blood and the severity of acute cholecytitis is a well‐known observation in adult patients, and several studies reported that the CRP value was a reliable predictor of severe conditions of inflammation and should be used in Tokyo classification . The correlation was not evaluated for the paediatric group, but it seemed similar to the observations for adults.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These findings confirmed the observation that AAC was concomitant with acute hepatitis rather than being induced by intrahepatic cholestasis . The correlation between the C‐reactive protein concentration in the blood and the severity of acute cholecytitis is a well‐known observation in adult patients, and several studies reported that the CRP value was a reliable predictor of severe conditions of inflammation and should be used in Tokyo classification . The correlation was not evaluated for the paediatric group, but it seemed similar to the observations for adults.…”
Section: Discussionsupporting
confidence: 75%
“…In the absence of reliable laboratory markers, the diagnosis of AAC is arrived at based on abdominal ultrasonography, with patients exhibiting thickening of the gallbladder wall (>3 mm), pericholecystic fluid, and mucosal membrane sludge. The combination of these ultrasonographic criteria, combined with the absence of gallstones and the elevation of C‐reactive protein as the separate biochemical marker, translated into the diagnosis of AAC in children …”
Section: Discussionmentioning
confidence: 99%
“…Grade I (mild) comprises cases other than Grades II and III, with lower risk of death and surgical risk that can easily be treated by laparoscopic cholecystectomy (LC). Since the Tokyo Guidelines (TG) have become widely known worldwide, recent multidirectional studies have evaluated the TG13 severity grading criteria for AC . In Tunisia, the spread of the TG has increased the rate of LC, significantly reducing preoperative and total hospital stay without increasing intra‐ and postoperative complications ; in Taiwan, Cheng et al.…”
Section: Introductionmentioning
confidence: 99%
“…Grade I (mild) comprises cases other than Grades II and III, with lower risk of death and surgical risk that can easily be treated by laparoscopic cholecystectomy (LC). Since the Tokyo Guidelines (TG) have ORIGINAL ARTICLE become widely known worldwide, recent multidirectional studies have evaluated the TG13 severity grading criteria for AC [2][3][4][5][6][7][8][9][10][11][12]. In Tunisia, the spread of the TG has increased the rate of LC, significantly reducing preoperative and total hospital stay without increasing intra-and postoperative complications [2]; in Taiwan, Cheng et al mentioned the complication rate and the length of hospital stay increased along with the severity grade of the TG [3]; and in Japan, too, a significant correlation has been reported between severity grade and both prolonged postoperative hospital stay and medical cost [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among recent reports, studies of CRP stand out in particular. One study that addressed the association between CRP and the TG13 severity grading criteria found that a CRP level >7.065 mg/dl may be considered as Grade II with 75% sensitivity and 96.5% specificity [26]. Another study investigating the association between WBC count, CRP, and histopathological findings found that CRP has a better discriminative power than WBC count in most forms of AC and is a useful diagnostic marker of AC [27].…”
Section: Discussionmentioning
confidence: 99%